Analysis of Student Learning Styles as an Implementation of Differentiated Learning Strategies in the Indonesian Education Merdeka Curriculum - Sati; Aiman Faiz; Lia Yulianasari (Jurnal Elementaria Edukasia, 2024)
The aim of this research is to explore the relationship between student learning styles which have implications for student learning outcomes in elementary schools, with a focus on the implementation of differentiated learning in the Independent Curriculum. Qualitative research methods were used to collect data from class IV students at SDN 1 Waleddesa. Data was collected through observation and interviews regarding student learning styles. The research results revealed that students' learning style patterns resulted in visual (4 people), auditory (4 people) and kinesthetic (2 people) learning styles. Observations show that with the strategic abilities of teachers who are skilled in designing responsive learning, they are able to provide implications for students' diverse learning experiences according to their needs and are able to increase student achievement under the Independent Curriculum Framework in Elementary Schools. With differentiated learning strategies, students will be able to achieve their optimal learning potential, according to the characteristics and tendencies of each individual student as implemented by teachers at SDN 1 Waleddesa. The implications of this research emphasize that to meet students' learning styles, teachers need to learn models, approaches, strategies and methods that lead to differentiated learning as in the Merdeka curriculum.